A Framework for Reaching Agreement on Climate Change: Morals, Self-Interest, and Strategy - TSCHANG, F. Ted (Institutional Knowledge at Singapore Management University, 1997)
This paper examines why negotiations following the Framework Convention on Climate Change (FCCC) have stalled and makes suggestions on how to circumvent the obstacles. In particular, the paper: - illustrates how current barriers to international agreement on climate change (CC) decompose into the separate components-self-interest, morality and strategy and discuss how the recent country positions are mixing them. - discusses some elements of a conceptual framework that will serve as a benchmark for assessing the feasibility of a proposal for a CC agreement. - discusses a few modest proposals that could potentially end the current stalemate, and also the potential hurdles in implementing them.